2017
DOI: 10.1186/s41606-017-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the symptom frequency of rapid eye movement sleep behavior disorder according to disease duration

Abstract: Background: This descriptive study was conducted to examine the changes in the symptom frequency in patients with rapid eye movement (REM) sleep behavior disorder (RBD) without medical intervention, in order to determine the association of RBD symptom frequency with disease duration. Methods: Data were collected from 70 consecutive RBD patients who visited the Sleep Clinic in Shiga University of Medical Science. RBD symptom frequencies at the first visit to the clinic were quantified based on the reports by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Therefore, patients with RBD and MH can be considered a group in which neurodegeneration has progressed further compared to patients without MH. There were no significant differences in RBDSQ scores between the longer/shorter disease duration groups (RBD with/without MH), which is consistent with the findings that symptom frequency of RBD peaks after 2–8 years of disease duration, after which the frequency decreases 47 . Among the RBD without MH group (at baseline), one patient presented MH and was subsequently diagnosed with DLB during follow‐up (Table S3).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, patients with RBD and MH can be considered a group in which neurodegeneration has progressed further compared to patients without MH. There were no significant differences in RBDSQ scores between the longer/shorter disease duration groups (RBD with/without MH), which is consistent with the findings that symptom frequency of RBD peaks after 2–8 years of disease duration, after which the frequency decreases 47 . Among the RBD without MH group (at baseline), one patient presented MH and was subsequently diagnosed with DLB during follow‐up (Table S3).…”
Section: Discussionsupporting
confidence: 84%
“…There were no significant differences in RBDSQ scores between the longer/ shorter disease duration groups (RBD with/without MH), which is consistent with the findings that symptom frequency of RBD peaks after 2-8 years of disease duration, after which the frequency decreases. 47 Among the RBD without MH group (at baseline), one patient presented MH and was subsequently diagnosed with DLB during follow-up (Table S3). From a different perspective, all five patients who progressed to phenoconversion presented with MH before phenoconversion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the RBDSQ-J score of our population was lower than in the previous report (53), and the average disease duration was rather long: ∼10 years after symptom emergence. The RBDSQ-J score may have been low due to the long disease duration of iRBD (77). According to a longitudinal observational study of patients with a long disease duration of iRBD, almost all subjects showed multiple features of neurodegeneration including autonomic dysfunction after a follow-up of at least 10 years (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study in Japan has reported that there was no association between RBD symptom frequency and disease duration, implying that the clinical symptoms of RBD may not be affected by disease progression. 32 As another factor for poor treatment outcomes, we found the presence of comorbid PLMS and poor treatment outcomes. Periodic limb movement during sleep is a common comorbid problem in patients with RBD, 33,34 and these 2 disorders share a pathophysiology, including dysfunction of the central dopaminergic system.…”
Section: Discussionmentioning
confidence: 68%